2014
DOI: 10.1371/journal.pone.0092737
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Human Breast-Cancer Derived Cell Line Stably Expressing a Bioluminescence Resonance Energy Transfer (BRET)-Based Phosphatidyl Inositol-3 Phosphate (PIP3) Biosensor

Abstract: Stimulation of tyrosine kinase receptors initiates a signaling cascade that activates PI3K. Activated PI3K uses PIP2 to generate PIP3, which recruit Akt to the plasma membrane through its pleckstrin homology (PH) domain, permitting its activation by PDKs. Activated Akt controls important biological functions, including cell metabolism, proliferation and survival. The PI3K pathway is therefore an attractive target for drug discovery. However, current assays for measurement of PIP3 production are technically dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…Our NAT and NEO BRET sensors precisely portrayed different ligands (IGF-1, Insulin or EGF) induced differential activation of ERK1/2 and PIP3-AKT in A2780 and MCF7 cell lines with maximal activation caused by IGF-1. Such increased level of AKT activation was earlier reported in MCF7 cells stimulated with IGF-1 compared to EGF stimulation [26] . Presence of specific kinase inhibitors (wortmannin and U0126), RTK inhibitor (PPP) and inactivating mutations (K14A-PH-AKT) reversed the IGF-1 induced increase in NAT and NEO BRET ratio, indicating the specificity of the sensors in dynamic monitoring of these key signalling events.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our NAT and NEO BRET sensors precisely portrayed different ligands (IGF-1, Insulin or EGF) induced differential activation of ERK1/2 and PIP3-AKT in A2780 and MCF7 cell lines with maximal activation caused by IGF-1. Such increased level of AKT activation was earlier reported in MCF7 cells stimulated with IGF-1 compared to EGF stimulation [26] . Presence of specific kinase inhibitors (wortmannin and U0126), RTK inhibitor (PPP) and inactivating mutations (K14A-PH-AKT) reversed the IGF-1 induced increase in NAT and NEO BRET ratio, indicating the specificity of the sensors in dynamic monitoring of these key signalling events.…”
Section: Discussionsupporting
confidence: 81%
“…The RLuc-PH-AKT/YFP-mem BRET sensor was reported to accurately monitor ligand induced PIP3 formation and AKT activation in MCF7 cells and used as prognostic tool to measure PI3K activity in human serum [26] . Similarly, Rluc-EKAR-Venus (REV), a BRET based ERK1/2 activity reporter was utilized to dynamically monitor ERK1/2 activation in primary cultures of hippocampal neurons isolated from 17 day embryonic mice in response to growth factors and pharmacological inhibitors [ 26 , 27 ]. Though both systems worked suitably on their own, the choice of donor luciferase has been shifted to nanoluciferase in recent years due to its superior brightness and quantum yield.…”
Section: Discussionmentioning
confidence: 99%
“…The inositol lipid-dependent PM binding of the luciferase linked to the lipid binding domain provided the basis for the non-specific BRET signal generated at the PM. A similar approach was used previously to measure PM PtdIns(3,4,5) P 3 [45], but in that study the co-expression of the BRET pair was provided by the generation of a double stable clone of MCF-7 cells allowing the measurement of the lipid pool shown by Akt-PH, which is known to bind both PtdIns(3,4,5) P 3 and PtdIns(3,4) P 2 [46, 47]. Intermolecular BRET applications become more reliable if the donor and the acceptor molecules are expressed in constant stoichiometric amounts, which is difficult to achieve with co-transfection.…”
Section: Discussionmentioning
confidence: 99%
“…RTK could lead to the activation of its downstream molecules SHC, GRB2, RAS, PI3K in turn [ 44 ], and promote to activate PIP2 into PIP3 [ 45 ], and then PIP3 activate APR2/3-F-actin via activating VAV/TIAM [ 46 ], RAC, BAIAP2 and WAVE2 in turn, and promote synthesis of actin [ 47 ]. In this study, VAV family member VAV1 and F - actin family members ACTA1 and ACTG2 were all up-regulated at 25 h, and further analysis of the physiological activities predicted by expression profiles of signaling pathway-associated genes indicated that the synthesis of actin was promoted.…”
Section: Discussionmentioning
confidence: 99%